The existence and numerical solution for a k-dimensional system of multi-term fractional integro-differential equations - De La Sen, Manuel; Hedayati, Vahid; Atani, Yasser Gholizade Gholizade; Rezapour, Shahram (Nonlinear Analysis: Modelling and Control, 2017)
First, we investigate the existence and uniqueness of solution for a k-dimensional system of multi-term fractional integro-differential equations. Also, we apply shifted Chebyshev and shifted Legendre polynomials to obtain an approximation solution for the k-dimensional system. Finally, we provide some examples illustrating the presented methods.
Keywords: Chebyshev polynomials; fixed point; Legendre polynomials; numerical solution; k-dimensional system of multi-term fractional differential equations